2012
DOI: 10.1007/s13280-012-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV-B and Elevated CO2 Impacts Sub-Arctic Shrub Berry Abundance, Quality and Seed Germination

Abstract: This study investigated the effects of longterm-enhanced UV-B, and combined UV-B with elevated CO 2 on dwarf shrub berry characteristics in a sub-arctic heath community. Germination of Vaccinium myrtillus was enhanced in seeds produced at elevated UV-B, but seed numbers and berry size were unaffected. Elevated UV-B and CO 2 stimulated the abundance of V. myrtillus berries, whilst UV-B alone stimulated the berry abundance of V. vitis-idaea and Empetrum hermaphroditum. Enhanced UV-B reduced concentrations of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…vascular meadow species (annual increase/decrease) [95] no. vascular heath species (annual increase/decrease) [95] f o r e s t birch tree-line change 1912-2009 (metre elevation shift) [16] understorey shrub change 1991-2009 (evergreens versus deciduous) [95,96] understorey change 1991-2009 (factor of change, shrubs versus others) [57] birch forestation 1906-1986 (degree of change 0-1) [58] aspen versus birch 1900-2007 (factor of change) [74] aspen species line 1904-2009 (dotted versus solid lines) [33] biomass change 1997-2010 (t ha -1 min/mean/max) [81] mountain and vegetation maps with courtesy of Lantmäteriet, Sweden rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120488 from 26.8 to þ0.68C across the study area (see figure 4 and electronic supplementary material, table 1). There is a notable diminishing of differences in the rate of warming between north-and south-facing slopes (see figure 2 and electronic supplementary material, table S1).…”
Section: Methods and Study Areamentioning
confidence: 99%
“…vascular meadow species (annual increase/decrease) [95] no. vascular heath species (annual increase/decrease) [95] f o r e s t birch tree-line change 1912-2009 (metre elevation shift) [16] understorey shrub change 1991-2009 (evergreens versus deciduous) [95,96] understorey change 1991-2009 (factor of change, shrubs versus others) [57] birch forestation 1906-1986 (degree of change 0-1) [58] aspen versus birch 1900-2007 (factor of change) [74] aspen species line 1904-2009 (dotted versus solid lines) [33] biomass change 1997-2010 (t ha -1 min/mean/max) [81] mountain and vegetation maps with courtesy of Lantmäteriet, Sweden rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120488 from 26.8 to þ0.68C across the study area (see figure 4 and electronic supplementary material, table 1). There is a notable diminishing of differences in the rate of warming between north-and south-facing slopes (see figure 2 and electronic supplementary material, table S1).…”
Section: Methods and Study Areamentioning
confidence: 99%
“…Given the way in which solar UV radiation, stratospheric ozone, and climate variables have multiple and often interdependent effects on terrestrial and agricultural systems, it is logical that these effects will modify the development, production and crop quality of agricultural crops. 9,[144][145][146] However, there are currently few studies focusing on the interplay of climatic variables on crop quality. 9,146 In contrast, many studies have reported both negative and positive effects of UV radiation and other climate variables on crop production.…”
Section: Implications Of Exposure To Uv Radiation and Climate Interacmentioning
confidence: 99%
“…Such field manipulations are already in development. 45,[228][229][230] Although UV-B radiation can affect food quality, this does not only involve phenolics, but a much broader range of metabolite classes including UV-regulated terpenoids, aromatic esters and others. 231 In peaches exposed to UV-B radiation, levels of the flavour-related monoterpene, linalool, decrease, while concentrations of sesquiterpene (E,E)-α-farnesene increase.…”
Section: Importance Of Secondary Metabolites In Agro-ecosystemsmentioning
confidence: 99%